Implementation of fast FFT design for 128-point using Radix-22 CFA - Bansal, Manish; Nakhate, Sangeeta (International Journal of Engineering and Technology, 2018)
In this paper, implementation of fast FFT design for 128- point using Radix-22 CFA is presented. This research uses a common factor algorithm which is based on Radix-22. A 2-point DFT butterfly structure is the lowest complexity structure and Radix-22 CFA is used to reduce logic and area by reducing the number of twiddle factors. The VHDL code is written and synthesized using Xilinx FPGA device xc7vx330t-3ffg1761 to implement the proposed design. This design is coded in VHDL and MATLAB. VHDL code is targeted to synthesize into Xilinx Virtex-7 FPGA and simulated into ModelSim PE Student Edition 10.4a. MATLAB code is simulated into MATLAB 2012. The proposed design achieves 149.822 MHz clock frequency, used 2802 slices on the Virtex-7 and SQNR 33.49 dB at 16-bit I/O word length.Â